1968
DOI: 10.1139/v68-401
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of thiyl radicals. V. The gas phase photolysis of methyl disulfide and ethyl disulfide mixtures in the presence of ethylene

Abstract: The gas phase photolysis of methyl disulfide and ethyl disulfide and their mixtures, in the presence and absence of ethylene, has been studied at 25 "C and 4 =.2300-2800 A. The,pure substrates give predominantly the corresponding thiol, whereas co-photolys~s y~elds methyl ethyl d~sulfide in appreciably larger yields.When ethylene is added, the substrates individually show a reduction in RSH rate and the formation of relatively small amounts of sulfides. I n their co-photolysis, added CzH4 does not appreciably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…The DMDS absorption spectrum reveals that 248 and 193 nm excitation are on different absorption features.26 Previous end product studies have shown that S-S bond scission occurs at 230-280 nm. [33][34][35] Our results confirm this interpretation. However, our study does not rule out the possible existence of other minor channels.…”
Section: Discussionsupporting
confidence: 89%
“…The DMDS absorption spectrum reveals that 248 and 193 nm excitation are on different absorption features.26 Previous end product studies have shown that S-S bond scission occurs at 230-280 nm. [33][34][35] Our results confirm this interpretation. However, our study does not rule out the possible existence of other minor channels.…”
Section: Discussionsupporting
confidence: 89%
“…Methyl radicals react with thiirane [ll] via simultaneous hydrogen abstraction and desulfurization and with CD3SH [12] via radical displacement, CH3 + CD3SH -CD3 + CH3SH. A similar type of displacement was obsened in the CH3S + C Z H~S S C~H~ system [13].…”
Section: Introductionsupporting
confidence: 59%
“…[1][2][3][4][5][6] Hence it is of fundamental importance to understand its photochemistry through study of energetics and structures of its photoionization products, and branching ratios as a function of photon energy in various dissociation channels. Numerous experimental measurements and theoretical calculations in the literature establish a reliable thermochemical database of organosulfur molecules, radicals, and ions.…”
Section: Introductionmentioning
confidence: 99%